2020
DOI: 10.1002/bdd.2243
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary physiologically based pharmacokinetic modeling of renally cleared drugs in Chinese pregnant women

Abstract: AimThe aim of this study was to build and verify a preliminary physiologically based pharmacokinetic (PBPK) model of Chinese pregnant women. The model was used to predict maternal pharmacokinetics (PK) of 6 predominantly renally cleared drugs.MethodBased on SimCYP Caucasian pregnancy population dataset, the preliminary Chinese pregnant population was built by updating several key parameters and equations according to physiological parameters of Chinese (or Japanese) pregnant women. Drug‐specific parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In addition, these models have other limitations as the exchange between the amniotic fluid and the fetus is not considered. Pregnancy PBPK model for renally eliminated drugs was also enhanced recently to account for ethnic differences by including specific details for Chinese pregnant populations [57]. Ongoing research regarding placental tissue structure and the consequences on fetal exposure will support enhancement of PBPK model for pregnancy applications [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these models have other limitations as the exchange between the amniotic fluid and the fetus is not considered. Pregnancy PBPK model for renally eliminated drugs was also enhanced recently to account for ethnic differences by including specific details for Chinese pregnant populations [57]. Ongoing research regarding placental tissue structure and the consequences on fetal exposure will support enhancement of PBPK model for pregnancy applications [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The second type consists of drug-related parameters, such as the plasma ratio, organ/blood partition coefficient, and permeability (Nestorov, 2003 ). Recently, PBPK models have been widely constructed to predict drug-related parameters (Chow et al, 2016 ; Pathak et al, 2019 ; Song et al, 2020 ). For example, Chow et al used a physiologically based model to predict drug solubility and effective permeability (Chow et al, 2016 ) to examine the potential impact of excipients on oral drug absorption.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…The fraction unbound in plasma (Fup) value and the blood-to-plasma concentration ratio (Rbp) were obtained from previous studies. 10,30 Model Verification Simulations were conducted using consistent clinical study conditions as reported in actual clinical trials, including demographic data and dosing regimens. The fold error of PK parameters, such as the area under the plasma concentration-time curve (AUC) and maximum plasma concentration (C max ) derived from the ratio of the observed and predicted in vivo values, and visual checks of the plasma concentration profiles were used to assess the predictive performance of the model.…”
Section: Establishment Of the Pbpk Modelmentioning
confidence: 99%